Effects of Bacillus Licheniformis BLI008 on Rhizoctonia Root rot Disease and Plant Ggrowth in Chilli - Somachandra, Kandangamuwa Pathirannahalage (2011)
Rhizoctonia root rot disease caused by Rhizoctonia solani Kühn is economically important on chilli (Capsicum annuum L.). Due to the increasing public concerns of fungicide usage, unavailability of resistant varieties and the limitations of cultural methods, biological control is emerging as a promising alternative to control R. solani in an environmentally-friendly way. Locally isolated Bacillus strain, Bacillus licheniformis BLI008, was tested against R. solani in-vitro to find out the antagonistic activity and the mechanism of antagonism. Strong mycelial growth reduction (74.79±0.48%) associated with frequent induction of a variety of morphological abnormalities and changes in mycelial color was observed in dual culture assay. Similar growth reduction (44.99±1.65%) and delaying of sclerotial germination occurred with the volatile compounds produced by the bacterium. Several methods of seed bacterization were tested under pot culture conditions in the presence of R. solani. A two days old nutrient agar culture of the bacterium applied as slurry on sterilized chilli seeds subsequently coated with CaCO3 provided best protection against damping-off. This method of seed bacterization significantly (P=0.05) increased seed germination (86%) and reduced post emergence damping-off (22.78%) over untreated seeds, and performed equally as chemical seed treatment. The control of root disease and bacterium mediated plant growth promotion was observed in greenhouse pot experiment. Measurements on root disease severity and growth parameters were taken 30 and 75 days after transplantation. The highest disease suppression was achieved when B. licheniformis BLI008 was inoculated (1x109 CFUs/mL) at the time of seed sowing as a drench to the nursery medium. Bacillus licheniformis BLI008 inoculation significantly increased shoot length (26.26%), root length (22.98%) total biomass (173.53%), and leaf chlorophyll content (13.64 mg/g of fresh weight) of chilli seedlings over the control at 30 days after transplantation. Those plants flowered earlier producing higher number (27.25) of flowers. In the presence of R. solani, bacterium mediated growth promotion was observed only on plants raised in bacterized nursery medium. They showed 12.46% increase in shoot length, 17.77% in root length and 99.00% in total biomass compared to untreated control. However, the responses varied with time, and were not consistent up to maturity. Among bacterized treatments challenged with R. solani, the highest (11.21 mg/g fresh weight) and lowest (8.98mg/g fresh weight) leaf chlorophyll values were reported in plants raised in bacterized medium and bacterized after four days of planting, respectively. The time taken for flower initiation and the number of flowers produced by bacterized treatments challenged with R. solani, except plants inoculated after four days of transplantation were similar to the control. The results of this study showed that the bacterial biocontrol agent tested has a great potential in controlling Rhizoctonia damping-off and root rot of chilli. Its plant growth enhancement can be considered as an added advantage in crop production.